Sustainable Recycling of Textile waste : Design of Eco-Socks in Monte Caseros, Corrientes - Maldonado, Paolo; Paniagua, Martín (My University, 2022)
One of the group members worked in a textile company in his city of origin, which is Monte Caseros, in the province of Corrientes. While working there, he witnessed many positive aspects of the company as well as others that could be improved. The textile company is called TN&PLATEX. It is in Monte Caseros, which is a city in Corrientes. This company produces a lot of dozens of socks per day. They are of different types, models and colours. To produce these socks several rags are produced as a result. Rags are rests of socks and rests of threads. They are not used so they are discarded. Since this company was founded in Monte Caseros, the job opportunities have increased, but the garbage produced by the city has increased greatly, too. The purpose of this presentation is to describe the current situation of textile production pollution in Monte Caseros, Corrientes. We are also going to analyze a solution consisting in reintroducing discarded rags into the production process. First, we are going to show the premises of company that is the focus of this work. Second, we are going to discuss the problem connected with rags production. Next, we are going to introduce the factors that give rise to this problem. After this, we are going to discuss the impact that the big production of rags has in the environment and company. Finally, we are going to describe our action plan to approach this problem. Resumen: Uno de los integrantes del grupo trabajaba en una empresa textil en su ciudad de origen, que es Monte Caseros, en el Provincia de Corrientes. Mientras trabajaba allí, fue testigo de muchos aspectos positivos de la empresa y de otros. eso podría mejorarse. La empresa textil se llama TN&PLATEX. Está en Monte Caseros, que es una ciudad de Corrientes. Esta empresa produce decenas de calcetines al día. Los hay de diferentes tipos, modelos y colores. Para producir estos calcetines se fabrican varios trapos. Los trapos son restos de calcetines y restos de hilos. Ellos son no se utilizan por lo que se desechan. Desde que se fundó esta empresa en Monte Caseros, las oportunidades laborales han aumentado, pero la basura La producción de la ciudad también ha aumentado considerablemente. El propósito de esta presentación es describir la situación actual de la contaminación de la producción textil en Monte Caseros, Corrientes. También vamos a analizar una solución consistente en reintroducir trapos desechados en el proceso de producción. En primer lugar, vamos a mostrar las premisas de la empresa objeto de este trabajo. En segundo lugar, vamos a discutir el problema relacionado con la producción de trapos. A continuación vamos a introducir los factores que dan lugar a esta problema. Después de esto, vamos a discutir el impacto que tiene la gran producción de trapos en el medio ambiente y compañía. Finalmente, vamos a describir nuestro plan de acción para abordar este problema.
Keywords: Inglés I; textile waste; eco-socks production; desperdicio textil; producción de medias ecológicas